KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU - Eriyanto Eriyanto (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2014)
The advantage of a nation no longer marked by the abundant natural wealth, but on the excellence of its human resources. A qualified education is one of the determinants the availability of excellent human resources. This will be achieved when the quality of education inputs, processes, outputs, teachers, facilities, infrastructure and expenses already met the standards properly. However, the major component of such a role is a teacher professionalism. This study used a qualitative approach, carried out in SMK 1 Panji Situbondo using case study design. Data collection techniques used include: (1) indepth interviews, (2) participation observation, and (3) documentation. Informants purposively selected using a sampling technique combined with snowball sampling. Data collected through these techniques were organized, interpreted, and analyzed within analysis as well as cross-case analysis. Credibility of the data checked by triangulation procedures, data verification / cross check, and check on the adequacy of the reference. While dependability and conformability reviewed by the supervisor.